PERGESERAN PEMAKAIAN TINGKAT TUTUR (BASA ALUS) BAHASA SASAK DI LOMBOK - Sudirman Wilian; Baiq Nurul Husaini (Masyarakat Linguistik Indonesia, 2018)
This study is aimed at finding out the factors influencing the decreasing use of Base Sasak Alus (honorific Sasak language) among the youths in Sasak, Lombok. Based on the quantitative and qualitative data gained through survey, interview and participant observation over several villages near and out of the three regency-city cetnters of Lombok, it was found out that the average youth mastery of the Sasak honorific vocabularies is far from adequate, and for the other their competence in using and constructing Sasak speech level is also ‘poor’, their score being respectively 56,58 and 51,55. There are some factors that are addressed to have triggered the decreasing use of the high language variety. First and for most important, the inadequate transfer of Base Alus from parents and elder family members to children in the home domain causes the lack of exposure of the high language variety and lead to the minimum opportunity for teenagers to listen and practice the honorific vocabularies in their home and outside. Second, out of their home in their neighbouring environment and societies they rarely heard people speaking in such respectful form of language, except in very formal situation such as feast, religious gathering, village offices. Third, the encroachment of Bahasa Indonesia in almost every domain of language use also influence the teenagers to tend to use Bahasa Indonesia when talking to ‘stranggers’ who come to their town or village eventhough they are Sasaks. Next is the change of value in marriage system for ‘noblemen’ family results in the loose system of the use of Base Alus. However, aristocrat families who consistently practice the use of the speech level among their family members, could contribute to the maintainance of the refined language much better, but their number is limited to the very small percentage of the ‘aristocrate’ family members themselves.